STUDENTS’ SPATIAL LITERACY IN GEOMETRIC TRANSFORMATIONS BASED ON VAN HIELE LEVELS OF THINKING - Muhammad Jufri; Bakri Mallo; Dasa Ismaimuza; Rahma Nasir; Mohammad Fadli (Universitas Sembilanbelas November Kolaka, 2026)
This study aims to describe students’ spatial literacy based on the Van Hiele levels of thinking in the topic of geometric transformations among eleventh-grade students at MAN 2 Palu. This research employed a descriptive qualitative approach with three students from class XI C as the subjects, selected based on the results of the Van Hiele thinking level test, each representing the visualization, analysis, and informal deduction levels. Data were analyzed using qualitative data analysis procedures. The findings show that students’ spatial literacy varies according to their thinking levels. Students at level 0 (visualization) have fairly good visualization skills but remain weak in reasoning and communication. Students at level 1 (analysis) demonstrate good spatial literacy in terms of visualization and reasoning, although their communication skills are not yet supported by logical justification. Students at level 2 (informal deduction) show strong spatial literacy across all indicators, including visualization, reasoning, and communication. Overall, the results indicate that higher Van Hiele thinking levels correspond to higher spatial literacy in solving geometric transformation problems.